Comparador Quantum-Óptico De Sequência De BITs E Aplicações - Sousa, Claudomir Pinto de (2021)
Quantum computing has attracted much attention because of its computational power compared to classical computing and, consequently, several quantum algorithms have been proposed in the literature. However, hardware able to implement such algorithms is still a challenge, In this work, we provide an optical setup for implementation of a quantum bit string comparator, QBSC, for polarization-based qubit, using the non-linear Kerr effect. The QBSC is an important structure for implementation of conditional statements in quantum algorithms.